Developing an Emotion- and Memory-Processing Group Intervention for PTSD with complex features: a group case series with survivors of repeated interpersonal trauma. Issue 1 (1st January 2018) - Clifford, Georgina; Meiser-Stedman, Richard; Johnson, Rebecca D.; Hitchcock, Caitlin; Dalgleish, Tim
ABSTRACT: Individuals who experience repeated interpersonal trauma exposure often present with posttraumatic stress disorder (PTSD) with more complex features. There is currently no consensus regarding whether current evidence-based interventions for PTSD need to be tailored to better account for these complex features. However, one recommended adaptation is to adopt a phase-based or sequenced approach involving three phases, each with a distinct function. This paper describes the development of a 12-session Emotion- and Memory-Processing Group Programme, adapted from Cloitre's Skills Training in Affective and Interpersonal Regulation (STAIR) phase-based treatment protocol. A single case series provided a preliminary examination of the group-based intervention's efficacy for three groups of women with a history of repeated interpersonal trauma and PTSD with complex features ( N  = 15; age 19–46 years) at The Haven Sexual Assault Referral Centre in London. Results revealed significant reductions in: PTSD, complex features of PTSD, and depression, along with improvements in process measures of maladaptive cognitions and emotion processing. Results from this case series demonstrate that an Emotion- and Memory-Processing Group Programme holds promise for treating individuals with a history of interpersonal trauma in outpatient settings, and provides evidence to warrant the completion of a feasibility trial.